Design and validation of an instrument to analyze the work of the occupational health and safety professional - Martinez-Rincon, Julian Andres; Rueda-Mahecha, Yohanna Milena; Silva-Giraldo, Cesar Augusto; Martínez García, Carlos Arturo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objective of this article is the validation of a data collection instrument to analyze the work of the occupational safety and health professional in a group of specialists and professionals in the discipline, such validation was carried out by expert judgment, using the content validity method, Aiken’s V and asymmetric confidence intervals (CI), a pilot test was also carried out to adjust the document, based on the results obtained, the instrument measures the constructs proposed to explore the work of the professional in the Colombian context.